2016
DOI: 10.1111/jth.13205
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS‐13 and von Willebrand factor predict venous thromboembolism in patients with cancer

Abstract: EssentialsCancer patients are at high risk of venous thromboembolism (VTE). In this study, cases and controls were cancer patients who did or did not develop VTE. von Willebrand factor (VWF) levels were higher if compared with controls and correlated with cancer stage. VWF and ADAMTS-13 are associated with the occurrence of VTE in cancer.Summary. Background: Patients with cancer are at high risk of venous thromboembolism (VTE). ADAMTS-13 regulates von Willebrand factor (VWF) activity, which plays a role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 52 publications
6
68
0
4
Order By: Relevance
“…Overall, this may identify VWF as a possible laboratory tool for risk stratification of cancer patients prone to develop VTE. These results are in accordance with Pépin et al, who found statistically significant increased levels of VWF in cancer patients with VTE compared to cancer patients without VTE. Interestingly, in their patient cohort there was no significant difference in the levels of ADAMTS‐13 or ADAMTS13/VWF between cancer patients with VTE or without.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, this may identify VWF as a possible laboratory tool for risk stratification of cancer patients prone to develop VTE. These results are in accordance with Pépin et al, who found statistically significant increased levels of VWF in cancer patients with VTE compared to cancer patients without VTE. Interestingly, in their patient cohort there was no significant difference in the levels of ADAMTS‐13 or ADAMTS13/VWF between cancer patients with VTE or without.…”
Section: Discussionsupporting
confidence: 92%
“…Cancer patients have been shown to have higher VWF levels and lower ADAMTS‐13 levels than the general population, often also in a stage‐dependent intensity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…acute lymphoblastic leukemia, colorectal cancer, bladder cancer, and ovarian cancer . Higher levels have been found to correlate with cancer stage and VTE occurrence in cancer patients . VWF also plays a role in hemostasis by binding FVIII and thus protecting the coagulation factor from proteolytic degradation and prolonging its half‐life in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of von Willebrand factor (vWF) are a risk factor for thrombus formation and progression. In 1971, it was first identified that the decrease of vWF could cause the occurrence of hemorrhagic diseases and, with the continuous studies on vWF, it was shown that the increase of vWF could promote the formation of thrombosis. vWF is synthesized by vascular endothelial cells and marrow megakaryocytes, which can connect collagen and platelets, initiate the coagulation process, and play a bridging role in thrombus.…”
Section: Discussionmentioning
confidence: 99%